2014
DOI: 10.1007/s10661-014-4185-8
|View full text |Cite
|
Sign up to set email alerts
|

Affects of different tillage managements on soil physical quality in a clayey soil

Abstract: This study, conducted in 2011, researches the effects of different tillage practices on the physical soil quality of clayey soil. This soil quality index (SQI) assessment was made by studying the changes in physical soil functions such as suitability for root development, facilitation for water entry, movement and storage, and resistance against surface degradation based on tillage management. When compared with the control parcel, statistically significant decreases were seen in the SQI with different tillage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Martínez et al (2016) reported that the soil pore system exhibited slightly higher specific diffusivity in the topsoil of mouldboard ploughing than in NT. Sağlam et al (2015) also reported that for heavy clayey soils, reduced tillage practices that included ploughing improved physical soil qualities for root development and water movement. It is believed that the inconsistent results arise from differences in climate, soil type and soil moisture level between humid and semi-arid regions.…”
Section: Discussionmentioning
confidence: 99%
“…Martínez et al (2016) reported that the soil pore system exhibited slightly higher specific diffusivity in the topsoil of mouldboard ploughing than in NT. Sağlam et al (2015) also reported that for heavy clayey soils, reduced tillage practices that included ploughing improved physical soil qualities for root development and water movement. It is believed that the inconsistent results arise from differences in climate, soil type and soil moisture level between humid and semi-arid regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, these current measures mainly focus on the optimization of fertilization methods, the selection of soil mineral modifiers and land consolidation to improve newly reclaimed cultivated land soil quality. Tillage treatment is a traditional soil improvement method, which can significantly regulate the dynamic balance of water, fertilizer, gas and heat in the soil 12 . It also affects the structural stability of the soil and the absorption of nutrients by crops, and finally affects crop yield 13 .…”
mentioning
confidence: 99%
“…As an important crop management practice, tillage has manifold influences on both the soil and crops, which are subjected to the local climate, soil type, soil water status, and tillage time (Sağlam et al, 2014). In order to balance the effect of different tillage practices, occasional tillage, also termed as "one-time tillage", has been evaluated as a potential tillage practice (Nunes et al, 2015;Blanco-Canqui and Wortmann, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Martínez et al (2016) reported that the soil pore system showed a slightly higher specific diffusivity in the topsoil after mouldboard ploughing as opposed to no-till. Sağlam et al (2014) also reported that for heavy clayey soils, tillage practices which included ploughing were thought to develop the physical soil qualities of root development and water movement.…”
Section: Discussionmentioning
confidence: 99%